LA MAESTRÍA EN CIENCIAS DE LA EDUCACIÓN DE AMPLIO ACCESO SU INFLUENCIA EN LOS MODOS DE ACTUACIÓN EN LOS UNIONENSES - Suárez Bello, Ana Julia (Atenas, 2012)
The work developed in the planification process, carrying out control of the Master’s degree in the Education Sciences of Wide Access, gives an answer to the guidelaine designed by the Education Ministry. The modest results that show the Unión de Reyes municipality have been fruit of the big efforts and the interchanges between teachers, students, famuly and the community that have made possible the mutual enrichment between all those agents who have participated in this process.